Doing business in asia (Deacons, 2006)
With the new, so-called global economy, doing-business-in-type books have been doing big business. As with the bewildering array of travel guides to choose from, these business guides are usually similar to one another, yet each will often have some unique feature that makes it worthy of consideration. Sanjyot heads an international training firm, and her guide has several distinctions. A number of the 11 Asian countries she profiles have been overlooked in most other books like this. Included here are Australia, China, Hong Kong, India, Indonesia, Malaysia, Singapore, Taiwan, Thailand, Vietnam. Each of the 11 entries gives a brief history and describes the country's geography, brief history, political structure, economy, corporate structure, work schedules (workday hours, holidays, etc.), and social customs (dining, drinking, visiting a home, gift giving, dress, etc.). Also provided are a few useful phrases, helpful telephone numbers and addresses (hospitals, chambers of commerce, diplomatic offices), and basic facts covering climate, electricity, currency, time zones, tipping, and transportation. In all, this is one of the better of the many books designed to help conduct business internationally.